The students’ perception towards the audit using Audit Command Language (ACL) software - Mega Trianico Puspaningrum (The Indonesian Accounting Review, 2014)
In line with the upsurge of computer application in companies in processing their information, auditor’s skill of computerized audit becomes very important. This study aimed to examine the effect of Perceived Usefulness and Perceived Ease of Use on the Computer Self- Efficacy. Samples were taken from a population of the ACL software users in Perbanas Surabaya. The data in this study was obtained through questionnaires. Of the 130 questionnaires distributed, 123 respondents were obtained. The data analysis that used in this study is the classical assumption test and multiple regressions. The result shows that perceived usefulness and perceived easeof use have no significant effect on computer self-efficacy, because there are other factors that affect the computer self-efficacy.